Dari Audit ke Laba: Menelusuri Pengaruh Kualitas Audit dalam Praktik Manajemen Laba Rill di Indonesia - Purwanti, Meilani; Mutaqqin, Aliyudin Ahsan (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study examines the impact of Audit Quality on Real Earnings Management in Indonesian companies, focusing on key factors such as firm size, Audit Fees, Auditor Specialization, and the timeliness of financial reporting. Using a quantitative approach with data from companies listed on the Indonesia Stock Exchange during the period from 2021 to 2023, this research aims to contribute to the understanding of how Audit Quality can influence the reduction of Earnings Management practices, particularly in emerging market contexts. The findings indicate that higher Audit Quality, especially when conducted by Big 4 Public Accounting Firms with industry specialization, significantly reduces Real Earnings Management. Additionally, the study reveals that higher Audit Fees and timely financial reporting also help mitigate Earnings Management practices. This research provides practical insights for regulators, investors, and corporate managers, emphasizing the importance of a robust audit process in ensuring the transparency and credibility of financial statements.